BMIDA-Directed Catalytic Asymmetric Transfer Hydrogenation for Enantioselective Access to α-Boryl Alcohols - Yang, Shuang; Fang, Xinqiang (Synlett, 2024)
The quest for general and highly efficient and enantioselective catalytic route to chiral alcohols remains a formidable challenge in asymmetric synthesis. Here, we highlight our recent work of asymmetric transfer hydrogenation (ATH) of N-methyliminodiacetyl (MIDA) acylboronates, showcasing a versatile platform for the efficient synthesis of enantiomerically enriched secondary alcohols. Acyl-MIDA-boronates harboring diverse (het)aryl, alkyl, alkynyl, alkenyl, and carbonyl substituents can be hydrogenated, yielding various α-borylated alcohols with high ee values. Crucially, the boron moiety can be easily transformed into other groups, allowing access to previously unattainable carbinols adorned with two structurally similar substituents. The enantioselectivity-directing role of BMIDA is elucidated by computational analyses, which stems from the CH–O electrostatic attraction between the η6-arene-CH of the catalyst and the σ-bonded oxygen atoms within BMIDA. This work represents the first asymmetric transformation on acylboronates and expands the domain of asymmetric transfer hydrogenation.
Keywords: asymmetric transfer hydrogenation; BMIDA; acylboronate; dicarbonyl boronate; α-boryl alcohol